Sharp Cu@Sn nanocones on Cu foam for highly selective and efficient electrochemical reduction of CO2 to formate - Chen, Chengzhen; Pang, Yuanjie; Zhang, Fanghua; Zhong, Juhua; Zhang, Bo; Cheng, Zhenmin (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Electrochemical reduction of aqueous CO2 into formate is subject to poor selectivity and low current density with conventional Sn-based catalysts owing to the inert nature of CO2 molecules and the low number of active sites. Recently, it has been demonstrated that alkali metal cations could greatly enhance selectivity for CO2 reduction by stabilizing the key intermediates, which leads to an effective solution to this problem by concentrating local metal cations through tailoring the catalyst structure. Herein, we synthesized spiky Cu@Sn nanocones over a macroporous Cu foam, which has a curvature radius of 10 nm, via facile electrochemical coating of a thin layer of Sn over the Cu nanoconic surface. A faradaic efficiency of 90.4% toward formate production was achieved, with a current density of 57.7 mA cm−2 at −1.1 V vs. a reversible hydrogen electrode, which far exceeds results achieved to date with state-of-the-art Sn catalysts. The performance should be attributed to the combined effects of a sharp conical feature that facilitates the enrichment of surface-adsorbed metal cations and the promotion of the mass transfer and active sites growth favored by the three-dimensional porous network.